Ressignificando o lar de origem: é hora de partir? uma leitura junguiana das relações familiares - Bedran, Angélica Coelho Gomes Tortorella (2017)
The number of young adults who remain in their parents' homes is a very recurrent phenomenon in Brazil and in the contemporary world scenario. The proposed qualitative research presents a family case study and an in-depth analysis of a daughter's relationship with her parents in the context of her intention to leave the parental home. The research instruments are constituted by a Play Family Genogram and clinical interview in the light of Analytical Psychology and its method of symbolic processing of research. The analysis of the results suggests that there are signs of cross idealization, excessive mothering and predominance of parenthood in relation to conjugality, as well as the presence of family complexes such as reported in the scientific literature which may be factors that delay leaving the parental home. This study reaches the proposed objectives and supports research that points to unconscious motivations that influence the exit or permanence in the home of origin and also demonstrates the effectiveness of the Play Genogram as an instrument for the perception of family ties and their conscious and unconscious connections